Vapor generation – atomic spectrometric techniques. Expanding frontiers through specific-species preconcentration. A review - Cerutti, Estela Soledad (2015)
We review recent progress in preconcentration strategies associated to vapor generation techniques coupled to atomic spectrometric (VGT-AS) for specific chemical species detection. This discussion focuses on the central role of different preconcentration approaches, both before and after VG process. The former was based on the classical solid phase and liquid?liquid extraction procedures which, aided by automation and miniaturization strategies, have strengthened the role of VGT-AS in several research fields including environmental, clinical, and others. We then examine some of the new vapor trapping strategies (atom-trapping, hydride trapping, cryotrapping) that entail improvements in selectivity through interference elimination, but also they allow reaching ultra-low detection limits for a large number of chemical species generated in conventional VG systems, including complete separation of several species of the same element. This review covers more than 100 bibliographic references from 2009 up to date, found in SCOPUS database and in individual searches in specific journals. We finally conclude by giving some outlook on future directions of this field.